The Deadlock Of The Decolonization Of Museums: When The Colonizer Becomes The Decolonizer - Küçük, Cihan (Lidé města, 2024)
Museums have traditionally served as custodians of cultural heritage, yet their history is inextricably linked with colonialism, often involving the acquisition of artefacts through coercion, exploitation, and violence. This article explores the complex and controversial legacy of national museums, particularly those with colonial histories, as they confront increasing demands for decolonization. By examining the historical context, including pivotal events such as the Berlin Conference and the Scramble for Africa, this article highlights the systemic looting and cultural destruction that have shaped these institutions. The analysis focuses on the ongoing global movement towards restitution and the challenges museums face in addressing their colonial pasts, exemplified by the British Museum and the Humboldt Forum. The latter, inaugurated in 2021, symbolizes the persistent influence of colonialism and the difficulties in achieving genuine decolonization. Despite efforts towards restitution and inclusivity, museums continue to grapple with deeply rooted colonial legacies, raising questions about their ability and willingness to undergo fundamental transformation. This article underscores the need for a comprehensive reassessment of museum practices and narratives, advocating for a more equitable approach to cultural preservation and representation.